Visual surveillance of a person: Legality issue - CHERNYAVSKY, SERHII; HRIBOV, MYKHAILO; YUSUPOV, VOLODYMYR (The Opole Studies in Administration and Law, 2023)
The relevance of the study stems from the legal ambiguity surrounding specific aspects of visual surveillance utilised by law enforcement agencies, journalists, private detectives, and other individuals with a need for it. The purpose of the study is to identify indicators that can differentiate between legal and illegal covert visual surveillance of individuals in public spaces, establish the circumstances under which such surveillance should be deemed a criminal offence, define the specific aspects of documenting this offence, and explore methods of proving the guilt of those responsible. Historical-legal, formal-legal, logical-normative, logical-semantic, sociological and statistical research methods are applied in the study. The criteria for the legality of covert visual surveillance of a person in publicly accessible places are: its conduct by authorised subjects (investigators or employees of operational units); implementation only within the framework of criminal proceedings (or proceedings in an intelligence gathering case); the existence of a decision of the investigating judge on permission to conduct visual surveillance of a specific person; strict compliance with the requirements of the Criminal Procedure Law regarding the procedure for conducting visual surveillance and restrictions established by the decision of the investigating judge. It is found that representatives of civilian professions can conduct visual surveillance in publicly accessible places only in an open way. Covert visual surveillance of a person to collect information about them constitutes a criminal offence consisting in violation of privacy. To bring illegal observers to criminal responsibility, factual data indicating the purpose of visual surveillance (collecting confidential information about a person), motives, time, place, means of committing the crime, and other circumstances are collected during the pre-trial investigation. The practical value of the paper is the possibility of using the obtained data to prevent illegal actions of private detectives, journalists, and other entities who secretly collect information about a person through visual surveillance, and to ensure effective investigation of such activities.